Manual de comunicación organizacional, un aporte a las organizaciones sin fines de lucro. Caso Fundación VASE (Voluntarios para la ayuda social del Ecuador) - Cueva Dávila, María Bernarda (2015)
This final work will result in a handbook of organizational communication for nonprofit organizations. First of all, the paper is covering the different concepts of communication, from the perspective of Paulo Freire in his Dialogic Action Theory; and Jürgen Habermas in his Theory of Communicative Action. Furthermore, it comprehends the different theories of communication and development. These theoretical concepts allow establishing it from an integral perspective. To get a better understanding of the connection between communication and organizations, the paper is covering several approaches of organizational communication theories. Additionally, there are different definitions of organizations, especially about non-profit organizations (NGOs), and they will, in this paper, be comprehended in the Ecuadorian context. Based on this, the main characteristic of the organization Foundation VASE (Voluntariado para la ayuda social del Ecuador) has been used as a case of study. The main objective of this work is to create a handbook of organizational communication for VASE with illustrative content based on the results of the diagnosis that is described in this paper. The handbook will provide an alternative solution in order to set up communication as a fundamental process in organizations, which in this particular case is applied to Foundation VASE.